2012
DOI: 10.1366/11-06458
|View full text |Cite
|
Sign up to set email alerts
|

In Situ High-Pressure and High-Temperature Experiments on n-Heptane

Abstract: The Raman spectroscopy of n-heptane was investigated in a moissanite anvil cell at ambient temperatures and a diamond anvil cell under pressures of up to ~2000 MPa and at temperature range from 298 to 588 K. The results show that at room temperature the vibration modes, assigned to the symmetric and antisymmetric stretching of CH(3) and CH(2) stretching, shifted to higher frequency according to quasi-linearity with increasing pressure, and a liquid-solid phase transition occurred at near 1150 MPa. The high-tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…It appears that the nonhydrostatic effects start small and gradually increase with increasing pressure. The hydrostatic limit of 3.5 GPa occurs where heptane is in its solid phase, as heptane freezes at 1.2 GPa. , Evidently, the solid phase remains soft enough at a lower pressure to serve as a hydrostatic medium below 3.5 GPa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It appears that the nonhydrostatic effects start small and gradually increase with increasing pressure. The hydrostatic limit of 3.5 GPa occurs where heptane is in its solid phase, as heptane freezes at 1.2 GPa. , Evidently, the solid phase remains soft enough at a lower pressure to serve as a hydrostatic medium below 3.5 GPa.…”
Section: Resultsmentioning
confidence: 99%
“…11 Heptane has a liquid-to-solid phase transition at 1.2 GPa. 12,13 Ma et al 14 reported observations of a new peak in the heptane X-ray diffraction (XRD) pattern appearing at a dspacing and pressure of 2.30 Å and 3 GPa, respectively, attributed to a rotator−rotator phase transition, along with a second phase transition at ∼7.5 GPa. The 3 GPa phase transition was apparently confirmed by Yamaguchi et al 15 based on IR transmission spectroscopy experiments.…”
Section: ■ Introductionmentioning
confidence: 99%